Digital Sex Work and Dual Labour–Technological Vulnerability: Cybersecurity Risks and Regulatory Gaps in Colombia and Latin America - Parra Sierra, Andrés Felipe (Scientific journal of social studies, 2026)
The expansion of platform-mediated work has reshaped contemporary forms of income generation, producing new labour configurations characterized by flexibility, technological dependence, and regulatory fragmentation. Digital sex work has emerged as a significant activity that combines the monetization of intimacy, socio-labour precarity, and exposure to technological risks, particularly in Latin American economies marked by high levels of structural informality and gender inequality. This study addresses the central problem of how risks related to labour security and cybersecurity are configured for digital sex workers in Colombia, considering the convergence of institutional under-protection, online violence, and regulatory gaps. The objective is to analyse these dynamics from a comparative socio-legal perspective in Latin America, identifying the transformations of platform-mediated sex work, the risks associated with cyber violence, and the limitations of existing regulatory frameworks. Methodologically, the study adopts a qualitative approach based on a critical narrative review that integrates contributions from labour law, gender studies, the sociology of digital work, and technology governance.The findings show that digitalization does not necessarily lead to formalization or improved working conditions. Instead, it reconfigures historical forms of vulnerability through algorithmic dependence, risk externalization, and the persistence of social stigma. The study concludes that effective protection of digital sex work requires comprehensive regulatory frameworks that integrate labour security, digital rights, and a gender perspective, as well as public policies aimed at technological literacy and institutional recognition of these labour trajectories.
Keywords: Digital sex work; digital platforms; labour precarity; cybersecurity; gender-based digital violence; labour regulation; digital rights; informality